2022
DOI: 10.1155/2022/4709019
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Minocycline on Cognitive Impairment, Hippocampal Inflammatory Response, and Hippocampal Alzheimer’s Related Proteins in Aged Rats after Propofol Anesthesia

Abstract: The aim of this study was to evaluate the effect of minocycline preadministration on cognitive dysfunction, hippocampal inflammatory response, and hippocampal senile dementia-related proteins induced by propofol anesthesia in aged rats. Sixty male SD rats, aged 20 months and weighing 340-410 g, were randomly divided into three groups: normal saline (NC) group, propofol group (prop), and minocycline (M) group. Prop group rats were injected intraperitoneally with 100 mg/kg propofol. The rats in group M were inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Neuroinflammation and synaptic damage are also important factors. Besides, AD or similar potential pathology may make individuals more vulnerable to the potential neurotoxic effects of surgical pressure and/or anesthetic exposure and increase the risk of postoperative cognitive impairment (Eikelenboom et al, 2011;Chang et al, 2021;Liang and Zhang, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Neuroinflammation and synaptic damage are also important factors. Besides, AD or similar potential pathology may make individuals more vulnerable to the potential neurotoxic effects of surgical pressure and/or anesthetic exposure and increase the risk of postoperative cognitive impairment (Eikelenboom et al, 2011;Chang et al, 2021;Liang and Zhang, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%